Environmental Control and Management Continuation through the Ruling of the State Administrative Court - Latif, Abdul; Cahyaningrum, Lulik Tri (KnE Social Sciences, 2024)
Changes in environmental law provisions that have the potential to cause inconsistencies in these decisions must be harmonized with the legal system. Without consistency in decisions regarding environmental public administration disputes, it will be difficult for the government to make decisions and guidelines for determining policies related to environmental protection and management. This research aims to determine the consistency of environmental administration dispute decisions in state administrative courts. The writing method uses a normative juridical approach with statutory regulations, the legal sources used were primary and secondary relating to state administrative law and environmental regulations, apart from that the author uses a case study approach. The results of the research show that the implementation of regulations related to state administrative decisions in the environmental sector is still inconsistent, with the government placing more emphasis on remedial (retroactive) efforts in environmental problems, manifested in the form of government intervention to restore environmental conditions after pollution and/or damage that occurs to the environment. Considering that the majority of environmental law enforcement is in the field of government administration, inconsistencies in environmental state administration decisions must be resolved immediately to realize good environmental protection and management. In fact, the decision of the state administrative court judge is not only intended to resolve a dispute but will also serve as a guideline for government agencies/officials in realizing sustainable environmental protection and management. Keywords: consistency, environment, protection, sustainability